Whole-genome sequencing reveals changes in genomic diversity and distinctive repertoires of T3SS and T6SS effector candidates in Chilean clinical Campylobacter strains - Katz, Assaf; Porte, Lorena; Weitzel, Thomas; Varela, Carmen; Muñoz-Rehbein, Cristina; Ugalde, Juan A.; Grim, Christopher; González-Escalona, Narjol; Blondel, Carlos J.; Bravo, Verónica (Frontiers in Cellular and Infection Microbiology, 2023)
Campylobacter is the leading cause of bacterial gastroenteritis worldwide and an emerging and neglected pathogen in South America. This zoonotic pathogen colonizes the gastrointestinal tract of a wide range of mammals and birds, with poultry as the most important reservoir for human infections. Apart from its high morbidity rates, the emergence of resistant strains is of global concern. In this study, we performed an in-depth analysis of the genome sequences of 88 Campylobacter jejuni and 2 Campylobacter coli strains isolated from clinical samples in Chile. We identified a high genetic diversity among C. jejuni strains and the emergence of prevalent clonal complexes, which were not identified in our previous reports. While 40% of strains harbored a mutation in the gyrA gene associated with fluoroquinolone resistance, no macrolide-resistance determinants were detected. Interestingly, gene clusters encoding virulence factors such as the T6SS or genes associated with long-term sequelae such as Guillain-Barré syndrome showed lineage-relatedness. In addition, our analysis revealed a high degree of variability regarding the presence of fT3SS and T6SS effector proteins in comparison to type strains 81-176, F38011, and NCTC 11168 and 488. Our study provides important insights into the molecular epidemiology of this emerging foodborne pathogen. In addition, the differences observed regarding the repertoire of fT3SS and T6SS effector proteins could have an impact on the pathogenic potential and transmissibility of these Latin American isolates, posing another challenge in characterizing the infection dynamics of this emergent and neglected bacterial pathogen.